Warm-keeping fabric and preparation method thereof

By using modified polyester fiber, volcanic rock fiber and synthetic fiber blending technology in warm-conserved fabrics, combined with the use of aerogel and modified carbon nanotubes, the problems of heavy, easy to generate electricity and sweat accumulation in existing fabrics are solved. , achieving the improvement of lightweight, warm, antibacterial, antistatic and mechanical properties.

CN119433794APending Publication Date: 2025-02-14JIANGSU SUNFENG SPECIAL MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411696770.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When improving warmth, existing warm-inclusive fabrics often use layers and thickening methods, resulting in heavy fabrics, texture and feel. At the same time, wool fabrics are easy to rub and electricity in winter, affecting their use, and heavy wear leads to sweat accumulation. Promote the reproduction of bacteria and viruses.

Method used

Modified polyester fiber, volcanic rock fiber and synthetic fiber are blended, and hollow porous structure is formed through air input and spinning treatment. Combined with the use of aerogel-filled and modified carbon nanotubes, it enhances the warmth, anti-static and Antibacterial properties.

Benefits of technology

The fabric is lightweight and warm, significantly improving antibacterial, antistatic and mechanical properties, ensuring that good performance remains after high washing times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005152273750000031
    Figure BDA0005152273750000031
  • Figure BDA0005152273750000041
    Figure BDA0005152273750000041
  • Figure BDA0005152273750000051
    Figure BDA0005152273750000051
Patent Text Reader

Abstract

The invention discloses a warm-keeping fabric and a preparation method thereof, and belongs to the technical field of garment fabrics. Comprising the following raw materials in parts by weight: 60-80 parts of polyester chips, 5-15 parts of modified carbon nanotubes, 10-20 parts of volcanic rock fibers and 20-30 parts of synthetic fibers. Wherein the volcanic rock fibers can improve the heat retention property and certain antibacterial property of the fabric; the modified polyester fibers are filled with aerogel, so that the warmth retention property and the portability of the fabric can be improved; compared with common carbon nanotubes, the modified carbon nanotubes have good compatibility with a polyester matrix, can significantly enhance the antibacterial, antistatic and mechanical properties of the fabric, and have long and stable properties; therefore, the fabric disclosed by the invention is excellent in heat retention property and portability, also has stable and efficient antibacterial, antistatic and mechanical properties, and has important application value in the technical field of garment fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of clothing fabrics, and in particular relates to a warm-keeping fabric and a preparation method thereof. Background Art

[0002] With the continuous improvement of the quality of life, people's functional requirements for clothing textiles and clothing have undergone a fundamental change, from the past economic and practical to comfort and functionality. People no longer regard the durability index of clothing textiles as the preferred indicator of consumption. The comfort and functionality of clothing materials and clothing have become the main factors considered by consumers. As the name suggests, thermal insulation fabrics require a certain degree of warmth retention, and of course, a certain degree of breathability and moisture conductivity. At present, for fabrics with thermal insulation effects, the design of thermal insulation fabrics often adopts the method of adding layers and thickening. Although it can achieve the purpose of thermal insulation, it increases the thickness and weight of the fabric, which reduces the texture and feel.

[0003] Wool fiber has good thermal insulation, moisture absorption and softness. Clothes made of wool fiber are comfortable to wear and have good warmth retention effect. However, wool fiber is expensive. Moreover, in winter, the air is relatively dry, and wool fabrics are easily electrified by friction, which affects their use. Finally, in winter, people wear thick clothes after exercise, and the sweat produced cannot be penetrated. It accumulates and provides a breeding ground for bacteria and viruses, leading to the massive growth of bacteria and viruses. In summary, it is urgent to invent a fabric with heat preservation, antistatic and antibacterial properties to meet the higher demands in the field of clothing fabric technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a warm-keeping fabric and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a warm-keeping fabric comprises the following steps:

[0007] A1, drying the polyester chips, mixing them with modified carbon nanotubes, adding them into a twin-screw extruder, inputting air after melt blending, and then performing spinneret treatment, and cooling to obtain hollow polyester;

[0008] A2, soaking the hollow polyester fiber obtained in step A1 into the aerogel slurry, stirring for 30 minutes, standing for 12 hours, taking it out, winding and forming it to obtain the spun yarn, and sequentially subjecting the spun yarn to bundling, drawing, tension heat setting, curling, oiling, and relaxation heat setting to obtain the modified polyester fiber;

[0009] A3. The modified polyester fiber, volcanic rock fiber and synthetic fiber obtained in step A2 are combined on a drawing frame to form a hollow textured yarn, which is then drawn and twisted on a roving frame, and finally further drawn and twisted on a spinning frame to form a blended yarn, which is finally woven on a shuttle loom to obtain a warm fabric.

[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of polyester chips, 5-15 parts of modified carbon nanotubes, 10-20 parts of volcanic rock fibers, and 20-30 parts of synthetic fibers.

[0011] Furthermore, in step A1, the air input rate is 1 L / min-2 L / min.

[0012] Furthermore, in step A3, the synthetic fiber is polyester fiber or nylon 66 fiber.

[0013] Through air input and spinning treatment, the polyester fiber produced has a hollow porous structure, which reduces the weight of the polyester fiber; by soaking in aerogel slurry, the aerogel is used to fill the hollow polyester, and because the aerogel is light and heat-insulating, the fabric is given lightness and warmth; the added volcanic rock fiber can improve the warmth of the fabric and has a certain antibacterial effect.

[0014] Furthermore, the aerogel slurry is prepared by the following steps:

[0015] Add silica aerogel powder, silane coupling agent KH-550 and ethanol aqueous solution into a high-speed disperser, and stir at a speed of 300-1500 r / min for 10-15 minutes at normal temperature and pressure to obtain aerogel slurry.

[0016] Furthermore, the raw materials are calculated in parts by weight as follows: 10-20 parts of silica aerogel powder, 2-10 parts of silane coupling agent KH-550, and 80-100 parts of ethanol aqueous solution.

[0017] Furthermore, the particle size of the silica aerogel powder is 5-100 μm.

[0018] The skeleton particles of silica aerogel have a small diameter and are porous materials, so a large number of reflective surfaces and reflective particles are formed inside it, which can reflect the radiant heat back and effectively reduce the thermal conductivity of radiation heat transfer to an extremely low level.

[0019] Furthermore, the modified carbon nanotubes are prepared by the following steps:

[0020] S1. In a three-necked flask equipped with a stirring device, triphenylphosphine (PPh3) was dissolved in toluene, chloroacetaldehyde was slowly added dropwise, and the temperature was raised to 55°C. The reaction was stirred for 3 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure to obtain intermediate 1; the ratio of triphenylphosphine, toluene and chloroacetaldehyde was 26.2g:100mL:7.6g;

[0021] Triphenylphosphine reacts with the chlorine group of chloroacetaldehyde to obtain the quaternary phosphonium product intermediate 1; the specific reaction process is as follows:

[0022]

[0023] S2. In a three-necked flask equipped with a stirring device, add intermediate 1 and N,N-dimethylformamide (DMF), stir evenly, then add 4,4'-azodiphenylamine and piperidine (condensing agent), stir and mix evenly, control the reaction temperature to 70°C, keep the reaction warm for 5 hours, and after the reaction is completed, remove part of the solvent by reduced pressure distillation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two is 3:2), and remove the eluent by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, N,N-dimethylformamide, 4,4'-azodiphenylamine, and piperidine is 30.5g:150mL:23.3g:15mL;

[0024] Under the action of the condensing agent, the aldehyde group on the intermediate 1 condenses with the amino group on the 4,4'-azodiphenylamine to form a C=N Schiff base structure. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 4,4'-azodiphenylamine, the intermediate 2 is obtained. The specific reaction process is as follows:

[0025]

[0026] S3, placing the carbon nanotubes in a conical flask, then adding mixed acid, ultrasonically treating in a 50°C water bath for 8 hours, cooling to room temperature after the reaction is completed, adding deionized water to dilute, centrifuging, and washing with anhydrous ethanol and deionized water for 4-5 times, drying, and grinding to obtain carboxylated carbon nanotubes; the mixed acid is prepared by mixing 98% by mass concentrated sulfuric acid and 38.8% by mass concentrated hydrochloric acid in a volume ratio of 2:1; the ratio of carbon nanotubes to mixed acid is 1g:100mL;

[0027] By subjecting carbon nanotubes to ultrasonic and oxidation treatment with strong acid, a certain number of carboxyl active groups can be introduced into the side walls and tops of carbon nanotubes to obtain carboxylated carbon nanotubes.

[0028] S4. In a three-necked flask equipped with a stirring device, the carboxylated carbon nanotubes were mixed with N,N-dimethylformamide, and ultrasonic treatment was performed for 30 minutes to uniformly disperse the carboxylated carbon nanotubes. Then, intermediate 2 and dicyclohexylcarbodiimide (DCC) were added, and magnetic stirring was performed for 2 hours. The mixture was ultrasonicated in a 65°C water bath for 2 hours, and then the water bath was removed and magnetic stirring was performed at room temperature for 8 hours. The mixture was filtered, washed with anhydrous ethanol for 3-4 times, dried, and ground to obtain modified carbon nanotubes. The ratio of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 2, and DCC was 1 g: 100 mL: 10.5 g: 17.4 g.

[0029] Under the action of DCC, -COOH on the surface of the carboxylated carbon nanotubes undergoes an amidation reaction with -NH2 on the intermediate 2, and organic molecules are grafted onto the surface of the carbon nanotubes to obtain modified carbon nanotubes. The specific reaction process is as follows:

[0030]

[0031] Carbon nanotubes are a kind of reinforcing material with high electrical properties. The modified carbon nanotubes are modified by grafting organic molecular chains through chemical bonding, that is, forming an organic layer on the surface of the carbon nanotubes, thereby enhancing the surface hydrophobicity of the carbon nanotubes, greatly improving the interface compatibility between the carbon nanotubes and the polyester matrix, and reducing the agglomeration of the carbon nanotubes, thereby promoting the uniform dispersion of the modified carbon nanotubes in the matrix, giving full play to the performance of the carbon nanotubes, and greatly improving the antistatic and mechanical properties of the matrix; in addition, the modified carbon nanotubes contain azobenzene, quaternary phosphonium salt and Schiff base structures, among which azobenzene as an antibacterial structure can combine with the chitin of bacteria, destroy the bacterial structure, play a bactericidal effect, and give the matrix a certain antibacterial property, and the azobenzene structure The carbon nanotubes contain benzene rings, which are hydrophobic groups. They can further improve the hydrophobicity of carbon nanotubes and the compatibility of carbon nanotubes with the matrix. The introduced quaternary phosphonium salt functional groups, in which the positively charged phosphonium ions are adsorbed on the surface of the bacteria, can interact with the negatively charged cell membrane of the bacteria, penetrate the cell wall, combine with the cell membrane, destroy the surface structure of the cell, and cause the intracellular substances to flow out. The respiratory function of the bacteria stops and causes cell death, which not only enhances the antibacterial property of the matrix, but also has better antibacterial activity than quaternary ammonium salts, and can also enhance the antistatic property of the matrix to a certain extent. Finally, the introduced C=N Schiff base structure can interact with bacterial proteins and enzymes, hinder the synthesis of bacterial nucleotides and amino acids, and synergize with quaternary phosphonium salts and azobenzene to greatly enhance the antibacterial property of the matrix.

[0032] It should be noted that the grafting of organic molecular chains onto carbon nanotubes can effectively prevent the migration and infiltration of organic molecules, thus ensuring the long-term stability of the performance of the modified carbon nanotubes.

[0033] Beneficial effects of the present invention:

[0034] The present invention blends modified polyester fiber, volcanic rock fiber and synthetic fiber to obtain a fabric, and the obtained fabric has the following effects:

[0035] 1. Volcanic rock fiber can improve the warmth retention and antibacterial properties of fabrics;

[0036] 2. Modified polyester fiber can improve the warmth and lightness of the fabric by filling it with aerogel;

[0037] 3. Compared with ordinary carbon nanotubes, the modified carbon nanotubes have better compatibility with polyester matrix, can significantly enhance the antibacterial, antistatic and mechanical properties of fabrics, and the performance is long-lasting and stable;

[0038] Therefore, the fabric of the present invention has excellent warmth retention and lightness, and also has stable and efficient antibacterial, antistatic and mechanical properties, and has important application value in the field of clothing fabric technology. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Embodiment 1

[0041] Preparation of modified carbon nanotubes:

[0042] S1. In a three-necked flask equipped with a stirring device, 26.2 g of triphenylphosphine was dissolved in 100 mL of toluene, 7.6 g of chloroacetaldehyde was slowly added dropwise, and the temperature was raised to 55° C. The mixture was stirred for 3 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure to obtain intermediate 1;

[0043] S2, in a three-necked flask equipped with a stirring device, add 30.5g of intermediate 1 and 150mL of N,N-dimethylformamide, stir evenly, then add 23.3g of 4,4'-azodiphenylamine and 15mL of piperidine, stir and mix evenly, control the reaction temperature to 70°C, keep the reaction for 5h, the reaction is completed, remove part of the solvent by reduced pressure distillation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / benzene, the volume ratio of the two is 3:2), and remove the eluent by rotary evaporation to obtain intermediate 2;

[0044] S3, placing 1 g of carbon nanotubes in a conical flask, then adding 100 mL of mixed acid (98% by mass concentrated sulfuric acid and 38.8% by mass concentrated hydrochloric acid in a volume ratio of 2:1), ultrasonically treating in a 50°C water bath for 8 h, after the reaction is completed, cooling to room temperature, adding deionized water to dilute, centrifuging, and washing with anhydrous ethanol and deionized water for 4-5 times, drying, and grinding to obtain carboxylated carbon nanotubes;

[0045] S4. In a three-necked flask equipped with a stirring device, mix 1 g of carboxylated carbon nanotubes with 100 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 30 min to evenly disperse the carboxylated carbon nanotubes. Then add 10.5 g of intermediate 2 and 17.4 g of dicyclohexylcarbodiimide, and perform magnetic stirring for 2 h. Place the mixture in a 65°C water bath and perform ultrasonic treatment for 2 h. Remove the water bath and perform magnetic stirring at room temperature for 8 h. Filter the mixture, wash with anhydrous ethanol 3-4 times, dry, and grind to obtain modified carbon nanotubes.

[0046] Embodiment 2

[0047] Preparation of modified carbon nanotubes:

[0048] S1. In a three-necked flask equipped with a stirring device, 52.4 g of triphenylphosphine was dissolved in 200 mL of toluene, 15.2 g of chloroacetaldehyde was slowly added dropwise, and the temperature was raised to 55° C. The reaction was stirred for 3 h. After the reaction was completed, the solvent was removed by reduced pressure distillation to obtain intermediate 1;

[0049] S2, in a three-necked flask equipped with a stirring device, add 61.0g of intermediate 1 and 300mL of N,N-dimethylformamide, stir evenly, then add 46.6g of 4,4'-azodiphenylamine and 30mL of piperidine, stir and mix evenly, control the reaction temperature to 70°C, keep the reaction for 5h, the reaction is completed, remove part of the solvent by reduced pressure distillation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / benzene, the volume ratio of the two is 3:2), and remove the eluent by rotary evaporation to obtain intermediate 2;

[0050] S3, placing 2 g of carbon nanotubes in a conical flask, then adding 200 mL of mixed acid (98% by mass concentrated sulfuric acid and 38.8% by mass concentrated hydrochloric acid in a volume ratio of 2:1), ultrasonically treating in a 50°C water bath for 8 h, after the reaction is completed, cooling to room temperature, adding deionized water to dilute, centrifuging, and washing with anhydrous ethanol and deionized water for 4 times in sequence, drying, and grinding to obtain carboxylated carbon nanotubes;

[0051] S4. In a three-necked flask equipped with a stirring device, mix 2 g of carboxylated carbon nanotubes with 200 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 30 min to evenly disperse the carboxylated carbon nanotubes. Then add 21 g of intermediate 2 and 34.8 g of dicyclohexylcarbodiimide, and perform magnetic stirring for 2 h. Place the mixture in a 65°C water bath and perform ultrasonic treatment for 2 h. Remove the water bath and perform magnetic stirring at room temperature for 8 h. Filter the mixture, wash it three times with anhydrous ethanol, dry it, and grind it to obtain modified carbon nanotubes.

[0052] Embodiment 3

[0053] Preparation of aerogel slurry:

[0054] 10 g of silica aerogel powder (particle size of 5 μm), 2 g of silane coupling agent KH-550 and 80 g of ethanol aqueous solution were added into a high-speed disperser, and stirred at a speed of 300 r / min for 10 min at normal temperature and pressure to obtain an aerogel slurry.

[0055] Embodiment 4

[0056] Preparation of aerogel slurry:

[0057] 20 g of silica aerogel powder (particle size of 100 μm), 10 g of silane coupling agent KH-550 and 100 g of ethanol aqueous solution were added into a high-speed disperser, and stirred at a speed of 1500 r / min for 15 min at room temperature and pressure to obtain an aerogel slurry.

[0058] Embodiment 5

[0059] A1. After drying 60 g of polyester chips, mix them with 5 g of modified carbon nanotubes prepared in Example 1, add them into a twin-screw extruder, input air (at a rate of 1 L / min) after melt blending, and then perform spinning treatment. After cooling, a hollow polyester is obtained;

[0060] A2, soaking the hollow polyester fiber obtained in step A1 into the aerogel slurry obtained in Example 3, stirring for 30 minutes, standing for 12 hours, taking out, winding and forming to obtain spun yarn, and sequentially subjecting the spun yarn to bundling, drawing, tension heat setting, curling, oiling, and relaxation heat setting to obtain modified polyester fiber;

[0061] A3. The modified polyester fiber obtained in step A2, 10 g of volcanic rock fiber and 20 g of polyester fiber are combined on a drawing frame to form a hollow textured yarn, which is then drawn and twisted on a roving frame, and finally further drawn and twisted on a spinning frame to form a blended yarn, which is finally woven on a shuttle loom to obtain a warm fabric.

[0062] Embodiment 6

[0063] A1. After drying 70 g of polyester chips, mix them with 10 g of modified carbon nanotubes prepared in Example 2, add them into a twin-screw extruder, input air (at a rate of 1 L / min) after melt blending, and then perform spinning treatment. After cooling, a hollow polyester is obtained;

[0064] A2, soaking the hollow polyester fiber obtained in step A1 into the aerogel slurry obtained in Example 4, stirring for 30 minutes, standing for 12 hours, taking it out, winding and forming it to obtain spun yarn, and then subjecting the spun yarn to bundling, drawing, tension heat setting, curling, oiling, and relaxation heat setting to obtain modified polyester fiber;

[0065] A3. The modified polyester fiber obtained in step A2, 15 g of volcanic rock fiber and 25 g of nylon 66 are combined on a drawing frame to form a hollow textured yarn, which is then drawn and twisted on a roving frame, and finally further drawn and twisted on a spinning frame to form a blended yarn, which is finally woven on a shuttle loom to obtain a warm fabric.

[0066] Embodiment 7

[0067] A1. After drying 80 g of polyester chips, mix them with 15 g of modified carbon nanotubes prepared in Example 2, add them into a twin-screw extruder, input air (at a rate of 1 L / min) after melt blending, and then perform spinning treatment. After cooling, a hollow polyester is obtained;

[0068] A2, soaking the hollow polyester fiber obtained in step A1 into the aerogel slurry obtained in Example 4, stirring for 30 minutes, standing for 12 hours, taking it out, winding and forming it to obtain spun yarn, and then subjecting the spun yarn to bundling, drawing, tension heat setting, curling, oiling, and relaxation heat setting to obtain modified polyester fiber;

[0069] A3. The modified polyester fiber obtained in step A2, 20 g of volcanic rock fiber and 30 g of nylon 66 are combined on a drawing frame to form a hollow textured yarn, which is then drawn and twisted on a roving frame, and finally further drawn and twisted on a spinning frame to form a blended yarn, which is finally woven on a shuttle loom to obtain a warm fabric.

[0070] Comparative Example 1

[0071] Ordinary carbon nanotubes of the same mass are used to replace the modified carbon nanotubes in Example 7, and the remaining steps are the same as those in Example 7 to obtain a fabric.

[0072] Comparative Example 2

[0073] Use commercially available thermal fabrics.

[0074] The fabrics of Examples 5, 6, 7, and Comparative Examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0075] The national standard GB / T 20944.2-2007 "Evaluation of antimicrobial properties of textiles - Part 2: Absorption method" was used to test the antibacterial rates of Escherichia coli and Staphylococcus aureus before and after washing 30 times;

[0076] The national standard GB / T 12703.2-2009 "Textile electrostatic test method Part 2: Charge surface density" was used to measure the charge surface density (uC / m 2 ) to test the antistatic performance (the smaller the charge surface density, the better the antistatic performance);

[0077] The national standard GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)" was used to determine the breaking strength.

[0078] Add 100° C. boiling water into a glass, fully wrap it with the fabrics of each embodiment and comparative example, place it at room temperature, remove the fabrics after 1 hour, and then measure the temperature of the water in the glass;

[0079] The measured results are shown in the following table:

[0080]

[0081] It can be seen from the above table that the antibacterial, antistatic and mechanical properties of the fabric prepared in the embodiment of the present invention are better than those of the comparative example, and the warming effect is good. The antibacterial property is still stable after washing 30 times. Therefore, the present invention has important application value in the field of clothing fabric technology.

[0082] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0083] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a warm-keeping fabric, characterized in that: The following steps are involved: A1, drying the polyester chips, mixing them with modified carbon nanotubes, introducing air after melt blending, and then spinning, cooling, to obtain hollow polyester; A2, soaking the hollow polyester fiber obtained in step A1 into the aerogel slurry, stirring for 30 minutes, standing for 12 hours, taking it out, winding and forming it to obtain the spun yarn, and sequentially subjecting the spun yarn to bundling, drawing, tension heat setting, curling, oiling, and relaxation heat setting to obtain the modified polyester fiber; A3. The modified polyester fiber, volcanic rock fiber and synthetic fiber obtained in step A2 are combined on a drawing frame to form a hollow textured yarn, which is then drawn and twisted on a roving frame, and finally further drawn and twisted on a spinning frame to form a blended yarn, which is finally woven on a shuttle loom to obtain a warm fabric.

2. The method for preparing a warm-keeping fabric according to claim 1, characterized in that: The modified carbon nanotubes are prepared by the following steps: S1, dissolving triphenylphosphine in toluene, slowly adding chloroacetaldehyde, stirring at 55°C for 3h, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 1; S2, after the intermediate 1 and N,N-dimethylformamide are stirred evenly, 4,4'-azodiphenylamine and piperidine are added, and the reaction is carried out at 70°C for 5 hours. After the reaction is completed, the intermediate 2 is obtained by vacuum distillation, column chromatography purification, and rotary evaporation; S3, placing the carbon nanotubes in a conical flask, then adding mixed acid, and ultrasonically treating in a 50°C water bath for 8 hours. After the reaction is completed, cooling to room temperature, adding deionized water to dilute, centrifuging, washing, drying, and grinding to obtain carboxylated carbon nanotubes; S4. Mix the carboxylated carbon nanotubes with N,N-dimethylformamide, ultrasonically treat for 30 minutes, then add intermediate 2 and dicyclohexylcarbodiimide, magnetically stir for 2 hours, ultrasonically treat in a 65°C water bath for 2 hours, magnetically stir at room temperature for 8 hours, filter, wash, dry and grind to obtain modified carbon nanotubes.

3. The method for preparing a warm-keeping fabric according to claim 2, characterized in that: In step S1, the ratio of triphenylphosphine, toluene and chloroacetaldehyde is 26.2 g:100 mL:7.6 g.

4. The method for preparing a warm-keeping fabric according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, N,N-dimethylformamide, 4,4'-azodiphenylamine, and piperidine is 30.5 g:150 mL:23.3 g:15 mL.

5. The method for preparing a warm-keeping fabric according to claim 2, characterized in that: In step S3, the ratio of carbon nanotubes to mixed acid is 1 g:100 mL.

6. The method for preparing a warm-keeping fabric according to claim 2, characterized in that: In step S4, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 2, and DCC is 1 g:100 mL:10.5 g:17.4 g.

7. The method for preparing a warm-keeping fabric according to claim 1, characterized in that: The aerogel slurry is prepared by the following steps: Silica aerogel powder, silane coupling agent KH-550 and ethanol aqueous solution were added into a high-speed disperser and stirred at room temperature and pressure to obtain aerogel slurry.

8. The method for preparing a warm-keeping fabric according to claim 7, characterized in that: The raw materials are calculated in parts by weight as follows: 10-20 parts of silica aerogel powder, 2-10 parts of silane coupling agent KH-550, and 80-100 parts of ethanol aqueous solution.

9. The method for preparing a warm-keeping fabric according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polyester chips, 5-15 parts of modified carbon nanotubes, 10-20 parts of volcanic rock fibers and 20-30 parts of synthetic fibers.

10. A warm-keeping fabric, characterized in that: Prepared according to the method according to any one of claims 1 to 9.